Website Security Analysis Using the OWASP10 Method (Case Study: almumtazparfumebatam.store) - Bagus Surya Pradhana (Jurnal Kewarganegaraan, 2024)
Al Mumtaz Parfume Batam is a perfume seller who is still doing business at home. To expand the scope of its business, an online store was created with the domain almumtazparfumebatam.store. Along with technological advances, the importance of security for a website is the main thing because it prevents attacks from irresponsible outsiders that can harm the ongoing business process. To find out how secure a website is against outside attacks, it is necessary to carry out a penetration testing (pentest) process where a tester simulates himself as an outsider trying to enter the network. This study aims to analyze and test the security of the almumtazparfumebatam.store website using the OWASP10 method in 2021. This method was chosen because it is always updated with information containing 10 attacks on the web that are often found. By doing this research, it is hoped that it can find possible security holes on the almumtazparfumebatam.store website and solutions to prevent them. With this research, it is also hoped that it can fix existing gaps so as to increase the security of the almumtazparfumebatam.store website and assist the website manager in preventing attacks that could be detrimental from irresponsible parties. Keywords: Website, Penetration Testing, OWASP Top 10